Can Child Marriage Law Affect Attitudes and Behaviour in the Absence of Strict Enforcement? Experimental Evidence from Bangladesh - Amrit Amirapu; M Niaz Asadullah; Zaki Wahhaj (Global Labor Organization (GLO), 2022)
In developing countries, one in four girls is married before turning 18, with adverse consequences for their own and their children's human capital. In this paper, we investigate whether laws can affect attitudes and behaviour towards child marriage - in a context in which the laws are not strictly enforced. We do so using a randomised video-based information intervention that aimed to accelerate knowledge transmission about a new child marriage law in Bangladesh that introduced harsher punishments for facilitating early marriage. Follow-up surveys documented an increase in early marriage among treated households if the father or family elders received the information. The findings allow us to distinguish between two competing theoretical channels underlying the effect of legal change and highlight the risk of backlash against laws that contradict traditional norms and practices.
Keywords: J12; J16; K36; 330; age of marriage; social norms; formal institutions; legal change